Design of Robust Control for Single Machine Infinite Bus System. (2015) - Dulau, Mircea; Bica, Dorin
Abstract: There are many considerations to be taken into when choosing a controller for a system. This paper presents the basic concepts of the robust control design, applied on electromechanical mathematical model of the synchronous generator. The second order model of Single Machine Infinite Bus (SMIB) system is used to develop a robust controller, by H-infinite (H∞ ) synthesis techniques, which guarantee stability and performance. Using Matlab software facilities, the frequency characteristics of sensitivities functions and the mechanical power time response in close-loop connection with the designed controller have been simulated.